Bacterial community of cushion plant Thylacospermum ceaspitosum on elevational gradient in the Himalayan cold desert - Řeháková, Klára; Chroňáková, Alica; Krištůfek, Václav; Kuchtová, Barbora; Čapková, Kateřina; Scharfen, Josef; Čapek, Petr; Doležal, Jiří (Frontiers in Microbiology, 2015)
Although bacterial assemblages are important components of soils in arid ecosystems, the knowledge about composition, life-strategies and environmental drivers is still fragmentary, especially in remote high-elevation mountains. We compared the quality and quantity of heterotrophic bacterial assemblages between the rhizosphere of the dominant cushion-forming plant Thylacospermum ceaspitosum and its surrounding bulk soil in two mountain ranges (East Karakoram: 4850–5250 m and Little Tibet: 5350–5850 m), in communities from cold steppes to the subnival zone in Ladakh, arid Trans-Himalaya, northwest India. Bacterial communities were characterized by molecular fingerprinting in combination with culture-dependent methods. The effects of environmental factors (elevation, mountain range, and soil physico-chemical parameters) on the bacterial community composition and structure were tested by multivariate redundancy analysis and conditional inference trees. Actinobacteria dominate the cultivable part of community and represent a major bacterial lineage of cold desert soils. The most abundant genera were Streptomyces, Arthrobacter and Paenibacillus, representing both r- and K- strategists. The soil texture is the most important factor for the community structure and the total bacteria counts. Less abundant and diverse assemblages are found in East Karakoram with coarser soils derived from leucogranite bedrock, while more diverse assemblages in Little Tibet are associated with finer soils derived from easily weathering gneisses. Cushion rhizosphere is in general less diverse than bulk soil, and contains more r-strategists. K-strategists are more associated with the extremes of the gradient, with drought at lowest elevations (4850 - 5000 m) and frost at the highest elevations (5750 - 5850 m). The present study illuminates the composition of soil bacterial assemblages in relation to the cushion plant Thylacospermum ceaspitosum in a xeric environment and brings important inform